Factors promoting or inhibiting normal birth - Samantha J. Prosser; Adrian G. Barnett; Yvette D. Miller (BMC, 2018)
Abstract Background In response to rising rates of medical intervention in birth, there has been increased international interest in promoting normal birth (without induction of labour, epidural/spinal/general anaesthesia, episiotomy, forceps/vacuum, or caesarean section). However, there is limited evidence for how best to achieve increased rates of normal birth. In this study we examined the role of modifiable and non-modifiable factors in experiencing a normal birth using retrospective, self-reported data. Methods Women who gave birth over a four-month period in Queensland, Australia, were invited to complete a questionnaire about their preferences for and experiences of pregnancy, labour, birth, and postnatal care. Responses (N = 5840) were analysed using multiple logistic regression models to identify associations with four aspects of normal birth: onset of labour, use of anaesthesia, mode of birth, and use of episiotomy. The probability of normal birth was then estimated by combining these models. Results Overall, 28.7% of women experienced a normal birth. Probability of a normal birth was reduced for women who were primiparous, had a history of caesarean, had a multiple pregnancy, were older, had a more advanced gestational age, experienced pregnancy-related health conditions (gestational diabetes, low-lying placenta, high blood pressure), had continuous electronic fetal monitoring during labour, and knew only some of their care providers for labour and birth. Women had a higher probability of normal birth if they lived outside major metropolitan areas, did not receive private obstetric care, had freedom of movement throughout labour, received continuity of care in labour and birth, did not have an augmented labour, or gave birth in a non-supine position. Conclusions Our findings highlight several relevant modifiable factors including mobility, monitoring, and care provision during labour and birth, for increasing normal birth opportunity. An important step forward in promoting normal birth is increasing awareness of such relationships through patient involvement in informed decision-making and implementation of this evidence in care guidelines.